Brain Functional Connectivity Is Different during Voluntary Concentric and Eccentric Muscle Contraction - Yao, Wan X.; Jiang, Zhiguo; Li, Jinqi; Jiang, Changhao; Franlin, Crystal G.; Lancaster, Jack L.; Huang, Yufei; Yue, Guang H. (Frontiers in Physiology, 2016)
Previous studies report greater activation in the cortical motor network in controlling eccentric contraction (EC) than concentric contraction (CC) of human skeletal muscles despite lower activation level of the muscle associated with EC. It is unknown, however, whether the strength of functional coupling between the primary motor cortex (M1) and other involved areas in the brain differs as voluntary movements are controlled by a network of regions in the primary, secondary and association cortices. Examining fMRI-based functional connectivity (FC) offers an opportunity to measure strength of such coupling. To address the question, we examined functional MRI (fMRI) data acquired during EC and CC (20 contractions each with similar movement distance and speed) of the right first dorsal interosseous (FDI) muscle in 11 young (20–32 years) and healthy individuals and estimated FC between the M1 and a number of cortical regions in the motor control network. The major findings from the mechanical and fMRI-based FC analysis were that (1) no significant differences were seen in movement distance, speed and stability between the EC and CC; (2) significantly stronger mean FC was found for CC than EC. Our finding provides novel insights for a better understanding of the control mechanisms underlying voluntary movements produced by EC and CC. The finding is potentially helpful for guiding the development of targeted sport training and/or therapeutic programs for performance enhancement and injury prevention.